Evaluating a new objective grading software for conjunctival hyperaemia. Issue 2 (April 2020) - Huntjens, Byki; Basi, Mandeep; Nagra, Manbir
Highlights: Objective grading of ocular hyperaemia shows greater consistency compared to subjective grading scales. Objective grading may lead to improved clinical monitoring particularly between experienced and novice ECPs. The outcomes from these subjective grading scales and automated software for redness grading are not interchangeable. Abstract: Background/ Aims: Standardised numeric grading scales are used in ophthalmic practice to improve consistency between clinicians in recording the severity of ocular conditions and to facilitate the monitoring of such changes. We investigated the intra- and inter-observer grading reliability and the agreement between subjective Cornea and Contact Lens Research Unit (CCLRU) and Efron grading scales as well as a new Advanced Ophthalmic Systems (AOS) software which uses an objective approach to grading conjunctival hyperaemia. Methods: One experienced observer graded n = 30 bulbar and n = 26 palpebral conjunctival hyperaemia images to 0.1 increments. Masked grading of randomised images was undertaken for all three methods, on two separate occasions. The agreement within and between the grading methods was assessed between sessions, and compared to the results of a novice observer. Results: There were no statistically significant differences (P > 0.05) between test and retest values. However, repeatability in the grading estimates of both bulbar and palpebral conjunctival hyperaemia was improved using the AOS grading method (R 2  = 0.998; Coefficient of Repeatability CoR 0.10–0.13), compared to Efron (R 2  = 0.926; CoR 0.62) and CCLRU (R 2  = 0.885–0.911; CoR 0.50–0.78). Intraclass coefficient correlations (ICC) improved inter-observer agreement using objective (> 0.995) versus subjective methods (0.853–0.959). Conclusion: These subjective and objective grading methods are not interchangeable. Due to the excellent repeatability and improved agreement between experienced and novice observers, the objective grading method provides a more consistent approach when grading ocular abnormalities and may achieve greater reliability in record keeping and clinical monitoring in the future.